New semi-synthetic scaffolds of isoalantolactone and their cytotoxic activity. (December 2016) - Kumar, Ashish; Kumar, Dharmesh; Maurya, Antim K.; Padwad, Yogendra S.; Agnihotri, Vijai K.
Graphical abstract: Sixteen new isoalantolactone (IAL 1 ) amino derivatives (IAL 2 – IAL 17 ) had been synthesized to enhance the water solubility. The compoundsIAL 2, 8, 9, 10, 12 and17 were found to be nearly as equally active asIAL 1 against all the three tested cell lines (SiHa, KB and HCT-116), whereasIAL 4 and16 against HCT116 cells. Highlights: Sixteen new amino derivatives of isoalantolactone were derivatized. Cytotoxicity of compounds were tested against three human cancer cells. Retention of cytotoxicity in eight compounds against tested cells observed. Abstract: In this study, a series of sixteen new isoalantolactone (IAL 1 ) amino derivatives (IAL 2 – IAL 17 ) had been synthesized.IAL 1 and synthesized analogs were evaluated for in vitro cytotoxicity against three human cancer cell lines including cervical cancer (SiHa), epidermoid carcinoma (KB) and colorectal carcinoma (HCT116). The compoundsIAL 2, 8, 9, 10, 12 and17 were found to be nearly active asIAL 1 against all the three tested cell lines, whereasIAL 4 and16 against HCT116 cells. Findings of the cytotoxicity had provided a correlation on the structure activity relationship ofIAL 1 and derivatized analogs against tested cells. The retention of cytotoxicity with enhanced water solubility in derivatized amino adducts includingIAL 2, 4, 8, 9, 10, 12, 16 and17 suggest that these adducts can further be tested for the detailed in vivo safety and anticancer studies with the aim to develop them as a drug.